The clinical course of COVID‐19 in pregnant versus non‐pregnant women requiring hospitalisation: results from the multicentre UK CA‐COVID‐19 study. (24th June 2021) - Crossette‐Thambiah, Christina; Nicolson, Phillip; Rajakaruna, Indika; Langridge, Alexander; Sayar, Zara; Perelta, Maria R.; Essex, Sarah; Oakes, Roderick; Mounter, Philip; Lewis, Sarah; Dutt, Tina; Scott, Ian; et al.
Summary: The impact of COVID‐19 infection on pregnant women remains relatively unknown but the physiological changes of pregnancy and hypercoagulability of COVID‐19 may further increase thrombotic risk. In this retrospective multicentre observational study, we report clinical characteristics and outcomes in 36 pregnant women requiring hospitalisation for COVID‐19 compared to a propensity‐matched cohort of non‐pregnant women. Pregnant women had a lower haemoglobin and higher lymphocyte counts but no differences in other haematological or biochemical parameters on admission compared to non‐pregnant women. There was no significant difference in the duration of hospitalisation; median two days (1–77) for pregnant versus eight days (1–49) for non‐pregnant women. A higher proportion of non‐pregnant women required mechanical ventilation [11/36 (31%) vs 3/36 (8%), P = 0·03] and received thromboprophylaxis with low‐molecular‐weight heparin (LMWH) within 24 h of admission [25/36 (69%) vs 15 /36(42%), P = 0·03] compared to pregnant women. One pregnant woman required extracorporeal membrane oxygenation. The rate of thrombosis was similar in both groups (one in each group). No women developed major bleeding or died. Data suggest that although non‐pregnant women had a severe clinical course, overall outcomes were not different between women with or without pregnancy. The use of thromboprophylaxis was inconsistent, demonstrating a need for establishing evidence‐based guidance for COVID‐19 during pregnancy.